1637 Ablative Therapies Versus Partial Nephrectomy for Small Renal Masses: A Systematic Review and Meta-Analysis. (12th October 2021) - Chan, V W S; Abul, A; Ng, H H L; Osman, F H; Wang, K; Cartledge, J; Wah, T M
Abstract: Introduction: The optimal management of small renal masses is unclear. Ablative therapies (AT) have been advocated as a potential alternative due to lower complication rates and non-inferior oncological outcomes. We performed a systematic review to compare AT and partial nephrectomy (PN) in patients with T1aN0M0 renal masses. Method: This review is registered on PROSPERO (CRD42020199099). A search was performed on Medline, EMBASE, and Cochrane CENTRAL to identify studies comparing AT and PN. Different modalities and approaches were analysed as subgroups. Outcomes include cancer-specific survival (CSS), overall survival (OS), recurrence-free survival (RFS), metastatic-free survival (MFS), postoperative complications, and change in renal function. Results: From 1, 351 identified records, 30 studies incorporating 85, 837 patients were included for meta-analysis. Patients receiving AT were found to have significantly worse CSS, OS, RFS when compared to patients receiving PN (p < 0.05). Patients undergoing AT have a non-inferior MFS and significantly fewer overall complications (HR: 0.79, 95% CI 0.41-1.51, p = 0.48; RR: 0.71, 95% CI 0.53-0.96, p = 0.03). Patients undergoing AT have a smaller decline in renal function post-operatively (SMD: 0.30, 95% CI 0.11-0.50). When limited to studies with propensity score matching, CSS and RFS are no longer significantly different between the two groups (HR: 1.54, 95% CI 0.67-3.52, p = 0.31, HR: 1.72, 95% CI 0.90-3.28, p = 0.10). Subgroup analyses did not show significant differences between different modalities and approaches of AT in all outcomes. Conclusions: AT is potentially non-inferior to PN when managing small renal masses, and more high-quality propensity score-matched studies with long follow-up time are needed to confirm the non-inferiority.